1893, N.C. Sess. Laws 356-57 - (:unkn) unknown (My University, 1893)
Pub. Laws, ch. 374, § 38: It shall be unlawful for any persons to organize a military company, or drill or parade under arms as a military body, except under the militia laws and regulations of this state; and no person shall exercise or attempt to exercise the power or authority of a military officer in this state unless he holds a commission from the governor, and any person offending against this act shall be guilty of a misdemeanor, and upon conviction shall be fined or imprisoned at the discretion of the court.
Keywords: MILITIAS